FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL DI PERUSAHAAN INDONESIA (PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2011-2014) - Nurul Firmanullah; Darsono Darsono (Diponegoro Journal of Accounting, 2017)
This study aims to examine factors affecting capital structure. This study uses a variable liquidity, profitability, asset structure, sales growth, asset growth, and business risk as independent variables.The population in this study consisted of all manufacturing companies listed in Indonesia Stock Exchange from 2011-2014. The sampling method in this research is purposive sampling. Total sample used in the analysis were 556 companies.The statistical methods used in this research is multiple linear regression analysis. The results of this study indicate that sales growth and business risk significantly influence capital structure while liquidity, profitability, asset structure, and asset growth has no effect on the capital structure.